The Influence of Work Family Conflict, Work Life Balance and Work Stress on Employee Performance in Generation Z in Yogyakarta - Sari, Rindi Purnama; Santoso, Awan (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This study aims to analyze the influence of work family conflict, work life balance and job stress on employee performance in generation Z in Yogyakarta. This research was conducted with a quantitative approach. Primary data collection was carried out by distributing questionnaires to a sample of 100 respondents of generation Z employees who live in Yogyakarta with statement items for all variables proven valid and reliable. The classical assumption test results in a normally distributed data regression model, no multicollinearity, and no heteroscedasticity. The results showed that: (1) Work Family Conflict has a negative and significant effect on Generation Z Employee Performance in Yogyakarta, (2) Work Life Balance has a positive and significant effect on Generation Z Employee Performance in Yogyakarta, (3) Job Stress has a negative and significant effect on Generation Z Employee Performance in Yogyakarta. This result is indicated by the significance value of the Work Family Conflict variable on Employee Performance of 0.003, the Work Life Balance variable on Employee Performance of 0.001, the Work Stress variable on Employee Performance of 0.038. From the results of this study it can be concluded that work family conflict, work life balance, and work stress have a significant influence on the performance of Generation Z employees in Yogyakarta